Geometric Meshing Simulation Analysis of Zero Spiral Bevel Gear - Zhou Jiaojun (Jixie chuandong)
In order to improve the meshing performance of zero spiral bevel gears,a modified roll method of processing parameter design method based on local synthesis method for pinion is proposed. The tooth contact analysis model including assemble errors is established. The contact path and transmission error curve are obtained by solving the nonlinear equations system. Then,the major axis of instantaneous contact ellipse is calculated based on differential geometry. The numerical example results show that,a middle- convex parabolic transmission error with the amplitude under a smaller range is achieved by using the modified roll method. The shaft angle misalignment has greatest effect on the meshing performance,which need to ensure the installation accuracy.